2007
DOI: 10.1016/j.biopsych.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning in Bipolar Disorder and Schizophrenia

Abstract: Background-Some patients with bipolar disorder (BD) demonstrate neuropsychological deficits even when stable. However, it remains unclear whether these differ qualitatively from those seen in schizophrenia (SZ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
147
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(176 citation statements)
references
References 52 publications
25
147
1
3
Order By: Relevance
“…32 However, owing to the limitations of using postmortem brain sections, future studies examining the consequences of these alterations to DA signalling and behaviour are required. Furthermore, it is interesting to note that patients with BD and schizophrenia had similar alterations in our study, which is consistent with the results of previous studies showing extensive overlap between these 2 disorders, including cognitive deficits, 33 genetic alterations, 34 changes in brain morphology 35 and oxidative stress. 36 Our results also showed that patients who are not prescribed antidepressants have lower TH and 3NT FRET than controls.…”
Section: Discussionsupporting
confidence: 92%
“…32 However, owing to the limitations of using postmortem brain sections, future studies examining the consequences of these alterations to DA signalling and behaviour are required. Furthermore, it is interesting to note that patients with BD and schizophrenia had similar alterations in our study, which is consistent with the results of previous studies showing extensive overlap between these 2 disorders, including cognitive deficits, 33 genetic alterations, 34 changes in brain morphology 35 and oxidative stress. 36 Our results also showed that patients who are not prescribed antidepressants have lower TH and 3NT FRET than controls.…”
Section: Discussionsupporting
confidence: 92%
“…42,43 In that respect, in five SZ kindreds of Celtic origin that were affected with language impairment or dyslexia, Bartlett et al 44 observed a parametric multipoint lod score of 3.92 with that cognitive impairment in a region of 13q that may overlap the present findings. As neurocognitive impairments have been shown to be shared by patients with SZ or BP, 45 and their unaffected relatives, 46,47 cognitive intermediate phenotypes might help to investigate further the mechanisms involved in chromosome 13q. 42 Also, the concurrent investigation of SZ and BP within the same study may bring advantages to modeling the disease, having in mind the probable joint implications of several susceptibility genes and of epigenetic effects involving environmental factors the nature and timing of which may contribute to explain commonalities as well as specificities in mechanisms underlying psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the relative severity of impairments across different cognitive domains tends to be very similar in bipolar disorder, psychotic major depression and schizoaffective disorders as compared to schizophrenia (e.g., 104,105,109,114).…”
Section: Cognition Across Psychotic Disordersmentioning
confidence: 99%